2020
DOI: 10.1101/2020.09.17.20196212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Anti-SARS-CoV-2 Convalescent Plasma in Patients Admitted for COVID-19: A Randomized Phase II Clinical Trial

Abstract: Background: Convalescent plasma (CP), despite limited evidence on its efficacy, is being widely used as a compassionate therapy for hospitalized patients with COVID-19. We aimed to evaluate the efficacy and safety of early CP therapy in COVID-19 progression. Methods: Open-label, single-center, randomized clinical trial performed in an academic center in Santiago, Chile from May 10, 2020, to July 18, 2020, with final follow-up August 17, 2020. The trial included patients hospitalized within the first 7 days of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Among them, four studies investigated different doses or durations of administration of the same intervention without comparisons with other interventions or SOC. 45, 46, 64, 71 Eight trials did not specify the outcomes of interest. 55, 58, 68, 81, 93, 101, 122, 123 Treatments in four trials were not connected in the network.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, four studies investigated different doses or durations of administration of the same intervention without comparisons with other interventions or SOC. 45, 46, 64, 71 Eight trials did not specify the outcomes of interest. 55, 58, 68, 81, 93, 101, 122, 123 Treatments in four trials were not connected in the network.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported for a randomized controlled trial conducted in Chile in which neutralizing antibody titers in donor plasma were not determined prior to transfusion. 19 In contrast, interim analysis of a randomized controlled trial from Spain with 81 randomized patients, reported that no patients progressed to mechanical ventilation or death among the 38 patients receiving convalescent plasma (0%), whereas six of 43 patients (14%) in the control arm did. 18 Mortality rates were 0% versus 9.3% at Days 15 and 29 for the active and control groups, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…4 Results from three randomized controlled studies and one large observational study have recently been released. 2, 17-19 The PLACID trial found convalescent plasma was not associated with significantly reduced mortality or progression to severe disease. 17 However, resolution of shortness of breath, fatigue, and negative conversion of SARS-CoV-2 viral RNA at Day 7 was higher in the transfused study arm.…”
Section: Discussionmentioning
confidence: 99%
“…The 91 included trials enrolled a total of 46,802 patients between January 18 (first recruitment) and October 4 (last recruitment). Included trials evaluated one or more drugs (n = 76, )or blood products (n = 9, [88][89][90][91][92][93][94][95][96] ) to treat patients with suspected or confirmed Covid-19 or drugs used as prophylaxis for patients at risk for Covid-19 (n = 6, [97][98][99][100][101][102] ). All but one of the trials were parallel group design (one trial was a cluster randomized design).…”
Section: Trial Characteristicsmentioning
confidence: 99%